Preclude Amputation in Surgical Cases -A study on Diabetic Dry Gangrene (Homoeopathy for All, 2024)
Gangrene is one of the serious  complications found mostly in  people who have diabetes or blood  vessel disease. Multidisciplinary  management of gangrene is  necessary to avoid complications  like amputation and permanent  disability. Homoeopathy can prevent  amputation in such condition by  stimulating the immune response  of the body. It helps in healing of  wound by increasing the blood  circulation of the affected area, it is  evident from this case of male with  age of 55 years who was suffering  from gangrene and treated within  4 months with Homoeopathic  similimum which was selected on  the basis of individualisation.
Keywords: Homoeopathy; Gan grene; Individualisation; Argentum metallicum